Influence of financial services on performance of women owned groceries in Meru Town, Kenya - Mung`ori,Kirema Boniface (Meru; Kirema Boniface Mung`ori, 2023)
Women workers throughout the world contribute to the economic growth and sustainable livelihood to their families and communities. Today the economic status of women is accepted as an indicator of society's stage of development. However, this is constrained by the inability of women to access financial services. This study investigated how availability of financial information influences the performance of women-owned groceries in Meru town. The study established how the availability of financial information, banking services, and credit services influences the performance of women-owned groceries in Meru town. The study is important to managers in their pursuit to finance micro and small enterprises. This study was based on social learning theory, Pecking Order theory and the theory of Credit Rationing. A descriptive survey design was adopted in this study. The target population in this study consisted of 4,333 women-owned groceries in Meru Town. A total of 353 participants were the sample. Primary data was collected using a questionnaire constructed by the researcher. Prior to the actual data collection process, a pilot study was conducted in Nkubu Town. Split half technique using Spearman Brown prophesy formula was employed to compute reliability co-efficient. A correlation coefficient of at least 0.7 was an indication that the data collection instrument reliable. Data was analyzed with an aid of SPSS version 22 as a tool of analysis. A multiple regression model was used to determine the degree to which each financial services influence women owned groceries. Data was presented in form of tables and figures. The study strictly adhered to ethical issues guiding research in terms of voluntary participation, anonymity and confidentiality. The study established that availability of saving facilities positively and significantly influence performance of women owned groceries in Meru Town. The study further indicated that accesses to credit facilities negatively and insignificantly influence the performance of women owned groceries in Meru Town. The study recommends that women owned grocery businesses should strive to access financial information to enable their enterprise to grow. Women owned grocery businesses should also endeavor to access saving facilities from financial institutions to enhance growth of their enterprises.
A Project submitted in partial fulfillment of the requirement for the degree of master of Business Administration of Meru University of Science and Technology
Includes references and appendices